Wide-Range Enhancement of Spectral Response by Highly Conductive and Transparent μc-SiOx:H Doped Layers in μc-Si:H and a-Si:H/μc-Si:H Thin-Film Solar Cells - Pei-Ling Chen; Po-Wei Chen; Min-Wen Hsiao; Cheng-Hang Hsu; Chuang-Chuang Tsai (International Journal of Photoenergy)
The enhancement of optical absorption of silicon thin-film solar cells by the p- and n-type μc-SiOx:H as doped and functional layers was presented. The effects of deposition conditions and oxygen content on optical, electrical, and structural properties of μc-SiOx:H films were also discussed. Regarding the doped μc-SiOx:H films, the wide optical band gap (E04) of 2.33 eV while maintaining a high conductivity of 0.2 S/cm could be obtained with oxygen incorporation of 20 at.%. Compared to the conventional μc-Si:H(p) as window layer in μc-Si:H single-junction solar cells, the application of μc-SiOx:H(p) increased the VOC and led to a significant enhancement in the short-wavelength spectral response. Meanwhile, the employment of μc-SiOx:H(n) instead of conventional ITO as back reflecting layer (BRL) enhanced the external quantum efficiency (EQE) of μc-Si:H single-junction cell in the long-wavelength region, leading to a relative efficiency gain of 10%. Compared to the reference cell, the optimized a-Si:H/μc-Si:H tandem cell by applying p- and n-type μc-SiOx:H films achieved a VOC of 1.37 V, JSC of 10.55 mA/cm2, FF of 73.67%, and efficiency of 10.51%, which was a relative enhancement of 16%.